Patient Participation in Surgical Treatment Decision Making from the Patients' Perspective: Validation of an Instrument - Liv-Helen Heggland; Torvald Øgaard; Aslaug Mikkelsen; Kjell Hausken (Nursing Research and Practice)
The aim of this paper is to describe the development of a new, brief, easy-to-administer self-reported instrument designed to assess patient participation in decision making in surgical treatment. We describe item generation, psychometric testing, and validity of the instrument. The final scale consisted of four factors: information dissemination (5 items), formulation of options (4 items), integration of information (4 items), and control (3 items). The analysis demonstrated a reasonable level of construct validity and reliability. The instrument applies to patients in surgical wards and can be used to identify the health services that are being provided and the areas that could strengthen patient participation.